RISK FACTORS IN HOSPITALIZED PATIENTS WITH STROKE POSITIVE ON SARS-COV-2-INFECTION - Petrovska, Monika; Matveeva, Niki; Miloshevski, Petar; Miloshevska, Mila; Stojkovska, Frosina (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Numerous reports indicate an increased number of strokes in the period after the peak of Covid 19, describing the presence of "COVID strokes" in young individuals with atypical thromboembolic events. The main goal of this investigation was to assess/identify risk factors and coexisting comorbidities, in patients first time hospitalized for diagnosis of stroke at the Neuropsychiatric Department at the Public Health Institution (PHI) General Hospital Ohrid, positive for Sars-Cov-2- infection, from 6 months prior to the day of hospital admission  in comparison to Sars-Cov-2 negative patients who met the same criteria. All 54 patients who met the criteria to be included in the study, after giving written consent, answered the modified  European Stroke Awareness Questionnaire (SAQ). Traditional stroke risk factors were highly prevalent in our cohort (Sars-Cov-2-infected patients with stroke) with more than 80% of individuals having had at least 1 documented risk factor such as obesity (significantly more prevalent in our cohort), sedentary lifestyle and presence of two or three coexisting comorbidities such as hypertension, dyslipidemia, diabetes, or heart disease.The investigation will contribute to the development of new models and strategies for the prevention of stroke in patients with Covid-19- infection. Key words: stroke, risk factors Covid-19, obesity, comorbidity